2009
DOI: 10.1016/j.jns.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neuropsychological outcome and DBS surgical trajectory and electrode location

Abstract: Background-The outcome literature of subthalamic nuclei (STN) deep brain stimulation (DBS) suggests that cognitive declines are commonly reported following surgery. We hypothesized that differences in electrode position and surgical trajectory may lead to a differential neuropsychological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
75
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 26 publications
7
75
2
Order By: Relevance
“…We thank Dr. Saleh for his comments regarding our manuscript, "Relationship between Neuropsychological Outcome and DBS Surgical Trajectory Electrode Location" [1]. We agree with several of the points that he raised, particularly those regarding the limitations of the current technology and the use of atlases in localization of a structure for any individual.…”
supporting
confidence: 55%
“…We thank Dr. Saleh for his comments regarding our manuscript, "Relationship between Neuropsychological Outcome and DBS Surgical Trajectory Electrode Location" [1]. We agree with several of the points that he raised, particularly those regarding the limitations of the current technology and the use of atlases in localization of a structure for any individual.…”
supporting
confidence: 55%
“…York et al [16] reported the occurrence of caudate penetration in 17 PD patients, but their focus was on trajectory angle and contact localization on verbal fluency. For the other 3 reports, neuropsychological examinations were comparable to those of our study, which enabled direct comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…York et al [16] investigated the relation of surgical lead trajectory and neuropsychological outcome, 6 months after STN DBS in PD patients. Their findings showed some significant changes in time but no significant relationships between the neuropsychological tests and the trajectory intersecting the caudate nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings showed some significant changes in time but no significant relationships between the neuropsychological tests and the trajectory intersecting the caudate nucleus. However, they found a relationship between mental state changes, verbal memory, fluency, depressive changes, and the electrode tip location in the STN, the distance from the active electrode to the midpoint of the AC-PC line, and the angle of the electrode tip to the midcommissural point in relation to the midsagittal plane [16]. Witt et al [8] also investigated the lead trajectory in PD patients who underwent STN DBS.…”
Section: Discussionmentioning
confidence: 99%